2017
DOI: 10.1021/acs.chemmater.7b01265
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Iron-Codoped Carbon Hollow Nanotubules as High-Performance Catalysts toward Oxygen Reduction Reaction: A Combined Experimental and Theoretical Study

Abstract: Heteroatom-doped carbons represent a unique class of low-cost, effective catalysts for the electroreduction of oxygen, with a performance that may rival that of commercial Pt/C catalysts. In the present study, Fe and N codoped porous carbon nanotubules were prepared by controlled pyrolysis of tellurium nanowire-supported melamine formaldehyde polymer core–sheath nanofibers at elevated temperatures. Electron microscopic studies showed the formation of hollow carbon nanotubules with the outer diameter of 35–40 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 86 publications
4
73
0
Order By: Relevance
“…Considering the difference in adsorption free energy (Δ G ads ) of the intermediates, the overpotential for the ORR/OER actually depends on the free energy variation (Δ G ) of the potential‐determining step with the highest energy barrier. The Δ G ads for O* (Δ G O* ) and OH* (Δ G OH* ) have been used as activity descriptors of MN x or MC x based SACs for ORR and OER mainly for the purpose of fast screening and rational design of new SACs. However, they are not related to the intrinsic structural characteristics of the active centers.…”
Section: Computational Insight Into the Structure–activity Correlatiomentioning
confidence: 99%
“…Considering the difference in adsorption free energy (Δ G ads ) of the intermediates, the overpotential for the ORR/OER actually depends on the free energy variation (Δ G ) of the potential‐determining step with the highest energy barrier. The Δ G ads for O* (Δ G O* ) and OH* (Δ G OH* ) have been used as activity descriptors of MN x or MC x based SACs for ORR and OER mainly for the purpose of fast screening and rational design of new SACs. However, they are not related to the intrinsic structural characteristics of the active centers.…”
Section: Computational Insight Into the Structure–activity Correlatiomentioning
confidence: 99%
“…[73] However, the N types contributing to OER/ORR are in serious disagreement, especially for pyridinic N and quaternary N. Reported by Liu and coworkers, [40] N-doped nanoribbon (N-GRW) with abundant edges exhibited outstand-ing bifunctional performance with 0.92 V of onset potential for ORR and 0.36 V overpotential at 10 mA cm À2 for OER in 1 M KOH. [73] However, the N types contributing to OER/ORR are in serious disagreement, especially for pyridinic N and quaternary N. Reported by Liu and coworkers, [40] N-doped nanoribbon (N-GRW) with abundant edges exhibited outstand-ing bifunctional performance with 0.92 V of onset potential for ORR and 0.36 V overpotential at 10 mA cm À2 for OER in 1 M KOH.…”
Section: Metal Freementioning
confidence: 99%
“…The onset and half‐wave potentials of FeN x ‐NCNT‐2‐NH 3 shifted positively to 0.95 and 0.84 V, respectively, which was in accordance with the CV results. The increased performance can be directly attributed to FeN x species, because it has been shown that metal nitrides, including M−N x active species, form more easily in an ammonia atmosphere, and M−N x species facilitate the binding of oxygen species . The importance of the FeN x species was also demonstrated by washing FeN x ‐NCNT‐2‐NH 3 with concentrated HCl to remove the FeN x active sites.…”
Section: Resultsmentioning
confidence: 99%